New geographic distribution area of the specie Nototriche hartwegii A.W. Hill, 1909 (Malvaceae: Malvales) in the wetlands of Central Ecuador - Juan Carlos Carrasco Baquero; Daisy Carolina Carrasco López; Verónica Lucía Caballero Serrano (Global Journal of Ecology - Peertechz Publications, 2022)
Nototriche hartwegii A.W. Hill, 1909 (Malvaceae: Malvales), is recorded for the first time in the province of Bolívar, in the wetlands of the Andean plateau of the Chimborazo Fauna Production Reserve (RPFCH). With this record, the endemic and limited distribution of this species to the wetlands of southern Ecuador, between 4100 and 4400 m.a.s.l., specifically in the provinces of Cañar and Azuay, is extended to the moorlands of central Ecuador.